In memory of Paolo Cantiani - Corona, Piermaria (Annals of Silvicultural Research, 2021)
This issue is dedicated to the memory of Paolo Cantiani, associate editor of this journal and senior researcher at the CREA Research Center for Forestry and Wood (Italy), recently passed away. Studying for passion rather than for work, he dedicated himself to research on silviculture and forest management planning. A free mind and determined character, he avoided simplifications in favor of simplicity, often providing simple solutions to complex problems, as his studies on the silviculture of Turkey oak and black pine forests demonstrate. Naturally kind and discreet, he was quick to provide an answer to those who asked and to offer his help to those who needed it. The memory of his wise and gentle smile, as well as of his writings, will always remain with us. A big hug from us all who had the privilege of working with you.